A macroscopic shear angle model for ultimate bearing capacity of glued laminated bamboo hollow columns under axial compression. (November 2022) - Su, Yi; Zou, Jun; Lu, Wei
Abstract: A hollow column has inherently greater ultimate bearing capacity and lateral stiffness than a solid column. However, the current studies find that the test value of the ultimate bearing load under axial loading is greatly different from the theoretical value for shear dislocation along weak joints. To accurately evaluate its ultimate bearing capacity, 21 Glued laminated bamboo hollow columns (GLBHCs) with three different slenderness ratios were fabricated and tested. It was found that the error between the theoretical value and tested value has great relation with slenderness ratios. The thickness of component members and the initial eccentric distance in the built-up column has little relation to the error. In the axial pressure failure stage, due to the change of section, the stress concentration at the vertical joint leads to large cracks, and the material shear dislocations occur, which results that the ultimate bearing capacity is significantly reduced. And the strain distribution does not comply with the plane-section assumption. In this paper, a macroscopic shear angle model was proposed. It is approximately considered that the section strain distribution still complies with the plane section assumption, despite the shear dislocation. On this basis, the ultimate bearing capacity formula of the GLBHC considering macroscopic shear angle was derived. Compared with test results, it can be found that the formula can accurately estimate the ultimate bearing capacity of GLBHCs.